Request strategies used in instant messaging in WhatsApp Groups (WAGs): Portraying the pragmatic competence of EFL students - Abourahim, Nawras B M; Suryati, Nunung; Basthomi, Yazid (Fakultas Sastra Universitas Negeri Malang, 2024)
This study aims to investigate the request strategies used by students and their lectur-ers through Instant Messaging (IM) in WhatsApp groups (WAGs). This study used a qualitative research design to analyze the language used by students and their lectur-ers in WAGs. The data was collected through the analysis of WAGs conversations be-tween students and their lecturers. Previous studies have extensively argued that stu-dents are less polite language users when sending texts to their lecturers, and the cur-rent study sought to examine the politeness strategies used by the students. The data analysis was carried out in the light the theory of speech acts proposed by Searle. The findings show that the subjects use certain strategies which contain politeness values. The Indonesian EFL context promotes more direct or indirect request strategies in and between the students and their lecturers. In addition, social power and social distance play a significant role in influencing the use of the strategies by students and lecturers in WAGs.